Application of Cow and Goat Urine in Traditional Systems of Medicines: A Brief Review: Application of Cow and Goat Urine in Traditional Systems of Medicines: A Brief Review - Sharma, Dr. Hemanta Kumar (International Journal of Pharmaceutical & Biological Archive, 2019)
In spite of the progresses in science and technology, India is well-known for its traditional system of medicine. Traditional use of medicine is practiced since the era of vedic. The Indian traditional system of medicine such as Ayurveda, Siddha, and Unani has a very rich history of their effectiveness. As India is a rich repository of herbal and medicinal plants, these traditional systems of medicine use herbal plants and minerals as the vital source for drugs. Along with the use of herbal plants, the Indian traditional system of medicine, especially Ayurvedic system, uses animal urine as a source of drug. In Ayurveda, the properties of the urine of eight different animals along with the human urine and also its uses are described. Basically, cow’s urine (CU) is used mainly for the treatment of various diseases in Ayurveda. Apart from CU, urine of the other animals such as goat, sheep, buffalo, elephant, horse, camel, and donkey were also used as remedies for the treatment of different diseases. An attempt has been made in this article to bring forth the traditional and therapeutic use of cow and goat urine (GU) and also highlights its efficacy. This article will provide brief information on cow and GU and their application in traditional practice of medicine which may help people working in this area.